2004
DOI: 10.1111/j.1600-0609.2004.00247.x
|View full text |Cite
|
Sign up to set email alerts
|

Different efficacy of mycophenolate mofetil as salvage treatment for acute and chronic GVHD after allogeneic stem cell transplant

Abstract: MMF would appear to be effective and safe for treating refractory chronic GVHD, yet not as effective for treating refractory acute gut GVHD. Accordingly, a prospective randomized clinical trial is warranted to assess the impact of MMF in the treatment of refractory GVHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 26 publications
(37 reference statements)
3
50
2
1
Order By: Relevance
“…First, clinical trials should use randomized designs whenever possible. Case-series reports and uncontrolled phase 2 studies suggested encouraging results with the use of MMF for treatment of steroid-refractory chronic GVHD, [6][7][8][9][10][11][12][13][14][15] but our results with the use of MMF for initial treatment of chronic GVHD offer no support for the use of MMF in the management of steroid-refractory chronic GVHD. Second, the field would benefit from a higher level of enthusiasm and support for enrolling patients in clinical trials.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…First, clinical trials should use randomized designs whenever possible. Case-series reports and uncontrolled phase 2 studies suggested encouraging results with the use of MMF for treatment of steroid-refractory chronic GVHD, [6][7][8][9][10][11][12][13][14][15] but our results with the use of MMF for initial treatment of chronic GVHD offer no support for the use of MMF in the management of steroid-refractory chronic GVHD. Second, the field would benefit from a higher level of enthusiasm and support for enrolling patients in clinical trials.…”
Section: Discussioncontrasting
confidence: 46%
“…Instead, the study was based on results of previous reports suggesting the efficacy of MMF for treatment of steroid-refractory chronic GVHD, [6][7][8][9][10][11][12][13][14][15] and the proposed effect size was based on the number of patients who could be enrolled in a multicenter study within a reasonable period of time. Even so, the negative results of this study did not simply reflect an overstringent primary endpoint or an unrealistic effect size because the much less stringent endpoint of complete response also did not show an advantage for the MMF arm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[31][32][33][36][37][38] Direct comparisons to other series examining MMF in refractory GVHD are difficult for several reasons. Basara et al reported an overall grade improvement in 65% of patients, where MMF was used as first-line therapy in addition to CSA and prednisolone on development of aGVHD or cGHVD.…”
Section: Discussionmentioning
confidence: 99%